Implementation of Authentic Materials in English Language Learning for Grade 1 Elementary School - Saputri, Helfiana; Kholid, M Ridho; Rahmawati, Istiqomah Nur (Universitas Nahdlatul Ulama Blitar, 2025)
The purpose of this study was to examine the effect of using authentic materials in improving English language skills of grade 1 students of SD Muhammadiyah 1 Bandar Lampung. Pre-experimental design with quantitative approach was used in this study. The research sample was 28 students taken using cluster sampling technique. Through pre-test and post-test, data was collected and then analyzed using Wilcoxon test to determine the effect of using Authentic Materials in English learning, with significance results between pre-test and post-test (p < 0.05), with an average pre-test score of 12.9 and post-test score of 70.0. The results of this study indicate that the use of authentic materials can be an effective teaching medium in improving the English language skills of grade 1 students.